Efficient computation of maximal orders in Artin–Schreier–Witt extensions. (November 2016) - Sutherland, Nicole
Abstract: An efficient algorithm for computing S -maximal orders and maximal orders in Artin–Schreier–Witt extensions of global function fields from pseudo bases is described. The running time of our algorithm is compared to that of Round 2 andFraatz (2005) . This completes our work on efficiently computing maximal orders in cyclic extensions of global function fields.